THE ROLE OF CYTOKINES IN THE IMMUNOPATHOGENESIS OF ACUTE PANTKEATITIS (The New Uzbekistan Journal of Medicine, 2025)
The article discusses the main issues of etiology, pathogenesis, classification, clinic, diagnosis and treatment of acute pancreatitis, taking into account the modern positions of the immune system, namely the cytokine system in the development of acute pancreatitis.